Single Bubble Breakage in Oil Under Stirring Conditions - Hasan, Basim Obaid (Al-Nahrain Journal for Engineering Sciences, 2022)
An experimental study on single bubble breakage in the stirred tank in oil as a continuous phase was carried out for a range of stirring speeds (220 to 430 rpm). The results are compared with bubble breakage in water that was conducted by Hasan et al. (2021) to investigate the effect of physical properties of continuous phase on the breakage rate. The breakage events in the impeller were captured and analyzed using a high speed camera. It was found that the breakage rate represented by breakage probability and a number of produced daughter bubbles (fragments) are directly proportional with the stirring speed. The breakage probability and number of produced daughter bubbles in oil was noticeably lower than that in water indicating the role the continuous phase viscosity plays in reducing the breakage rate.